Mitochondria Lead the Way: Mitochondrial Dynamics and Function in Cellular Movements in Development and Disease - Madan, Somya; Uttekar, Bhavin; Chowdhary, Sayali; Rikhy, Richa (Frontiers in Cell and Developmental Biology, 2022)
The dynamics, distribution and activity of subcellular organelles are integral to regulating cell shape changes during various physiological processes such as epithelial cell formation, cell migration and morphogenesis. Mitochondria are famously known as the powerhouse of the cell and play an important role in buffering calcium, releasing reactive oxygen species and key metabolites for various activities in a eukaryotic cell. Mitochondrial dynamics and morphology changes regulate these functions and their regulation is, in turn, crucial for various morphogenetic processes. In this review, we evaluate recent literature which highlights the role of mitochondrial morphology and activity during cell shape changes in epithelial cell formation, cell division, cell migration and tissue morphogenesis during organism development and in disease. In general, we find that mitochondrial shape is regulated for their distribution or translocation to the sites of active cell shape dynamics or morphogenesis. Often, key metabolites released locally and molecules buffered by mitochondria play crucial roles in regulating signaling pathways that motivate changes in cell shape, mitochondrial shape and mitochondrial activity. We conclude that mechanistic analysis of interactions between mitochondrial morphology, activity, signaling pathways and cell shape changes across the various cell and animal-based model systems holds the key to deciphering the common principles for this interaction.